Piezoelectric hydrogel, preparation method thereof and ultrasonic treatment device

By developing a piezoelectric hydrogel containing a variety of functional ingredients, and using ultrasound to induce the generating active oxygen, it solves the problem of a single function of traditional wound dressing, and realizes the multiple effects of wet wetting, promoting healing, and preventing infection.

CN119345447APending Publication Date: 2025-01-24JIANGSU ACOUSTIC IND TECH INNOVATION CENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411259616.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing wound dressings have a single function in promoting wound healing, making it difficult to achieve multiple effects of absorbing exudate, maintaining moisture, preventing bacterial infection, anti-inflammatory, antioxidant and promoting angiogenesis at the same time.

Method used

Develop a piezoelectric hydrogel containing methacrylated gelatin, potassium sodium niobate, polydopamine, polylactic acid, carboxymethyl chitosan, epidermal growth factor and glycerin, which can generate active oxygen through ultrasound induction and kill quickly. Kill wound bacteria and promote epidermal cell proliferation and differentiation.

Benefits of technology

It achieves the multiple effects of moistening the wound surface, promoting healing, and preventing infection, and improves the efficiency and effect of wound repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119345447A_ABST
    Figure CN119345447A_ABST
Patent Text Reader

Abstract

The invention relates to piezoelectric hydrogel, a preparation method thereof and an ultrasonic treatment device. The piezoelectric hydrogel comprises methacrylated gelatin, potassium sodium niobate, polydopamine, polylactic acid, carboxymethyl chitosan, epidermal growth factors and glycerin, the surface of the potassium sodium niobate is modified with the polydopamine, and the potassium sodium niobate, the polydopamine, the polylactic acid, the carboxymethyl chitosan, the epidermal growth factors and the glycerin are dispersed in the methacrylated gelatin. According to the invention, a biodegradable piezoelectric material is combined with an ultrasonic technology, when the piezoelectric hydrogel is used as a wound dressing and is attached to an epidermis wound, the piezoelectric material is induced by ultrasound to generate a large amount of active oxygen, and the active oxygen can quickly kill bacteria from the wound, so that the epidermis wound is repaired.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogels, and in particular to a piezoelectric hydrogel and a preparation method thereof, and an ultrasonic treatment device. Background Art

[0002] The skin is the largest organ in the human body and an important barrier to protect the human body. It plays a vital role in resisting harmful external environments and toxic substances, preventing bacterial infection, and reducing water and electrolyte loss. Injury or surgery can cause the skin to lose its integrity and easily cause microbial infection. Secondary infection of the wound surface remains one of the difficult problems in trauma treatment. There is a significant negative correlation between wound infection and regeneration, and the persistence of local infection seriously affects the formation of new tissue. Debridement alone cannot completely eliminate bacteria and their biofilms, resulting in recurrence of infection and prolonged wound healing.

[0003] Wound dressings are considered the most direct and effective method of wound care. However, traditional wound dressings are mostly gauze, bandages or sponges, which only have the single function of forming a physical barrier or absorbing exudates, and have a weak effect in promoting healing. In addition, these dressings may even cause re-injury during use, increasing treatment costs and patient burden. Therefore, the ideal dressing should not only absorb wound exudate and keep the wound moist, but also be biodegradable, protect the wound from bacterial infection, and have anti-inflammatory, antioxidant and angiogenic effects.

[0004] As a new type of highly water-containing polymer material, hydrogel is an ideal material for wound dressings due to its excellent biocompatibility and low immune response. However, traditional hydrogel materials have a single function and are difficult to meet the needs of complex biomedical applications. Summary of the invention

[0005] Based on this, it is necessary to provide a piezoelectric hydrogel and a preparation method and an ultrasonic therapeutic device that can achieve epidermal wound repair and have good biocompatibility and biodegradability.

[0006] A piezoelectric hydrogel comprises methacryloyl gelatin, sodium potassium niobate, polydopamine, polylactic acid, carboxymethyl chitosan, epidermal growth factor and glycerol, wherein the polydopamine is modified on the surface of the sodium potassium niobate, and the sodium potassium niobate, polydopamine, polylactic acid, carboxymethyl chitosan, epidermal growth factor and glycerol are dispersed in the methacryloyl gelatin.

[0007] In the piezoelectric hydrogel of the technical solution of the present invention, methacrylated gelatin is used as a hydrogel matrix with a multi-network structure for carrying other functional substances; polylactic acid is a biodegradable piezoelectric polymer; potassium sodium niobate is a soluble piezoelectric material with excellent piezoelectric properties; polydopamine is introduced to modify the surface of potassium sodium niobate, which is beneficial to improve biocompatibility; carboxymethyl chitosan can help epidermal wounds to stop bleeding and sterilize quickly. When the microenvironment of the epidermal wound reaches stability, with the continuous release of epidermal growth factor, the rapid proliferation and differentiation of epidermal cells are promoted, thereby achieving rapid healing and repair of epidermal wounds; epidermal growth factor can promote the rapid proliferation and differentiation of cells in epidermal wounds and accelerate the healing of epidermal wounds; glycerol is beneficial to improving the adhesion and moisturizing properties of piezoelectric hydrogels. The present invention combines biodegradable piezoelectric materials with ultrasonic technology. When the piezoelectric hydrogel is used as a wound dressing and attached to the epidermal wound, a large amount of active oxygen is generated by the piezoelectric material through ultrasonic induction. The active oxygen can quickly kill bacteria from the wound, thereby achieving epidermal wound repair.

[0008] In a feasible implementation, the mass ratio of the methacryloylated gelatin, the potassium sodium niobate, the polydopamine, the polylactic acid, the carboxymethyl chitosan, the epidermal growth factor and the glycerol is (80-160):(0.5-2):(0.1-0.5):(0.5-1):(0.1-0.5):(0.1-0.5):(40-80).

[0009] A method for preparing a piezoelectric hydrogel comprises the following steps:

[0010] The potassium sodium niobate powder and the polydopamine powder are dissolved in a buffer solution, and after sufficient reaction, solid-liquid separation is performed and the solid is retained to obtain potassium sodium niobate with the surface modified with polydopamine;

[0011] Dissolving the potassium sodium niobate with polydopamine on the surface and polylactic acid powder in a first organic solvent, mixing them evenly, performing solid-liquid separation and retaining the solid to obtain a mixture of potassium sodium niobate with polydopamine on the surface and polylactic acid; and

[0012] The mixture of sodium potassium niobate and polylactic acid modified with polydopamine on the surface, methacrylated gelatin, carboxymethyl chitosan, epidermal growth factor and glycerol are dissolved in water, mixed evenly, and then a photocuring agent is added, mixed evenly, and then a cross-linking reaction is carried out, and a piezoelectric hydrogel is obtained after sufficient reaction.

[0013] The preparation method of the piezoelectric hydrogel of the technical solution of the present invention is simple in process. The prepared piezoelectric hydrogel has good biocompatibility, is compatible with biological tissues, and supports cell adhesion, proliferation and differentiation, and is suitable for biomedical applications. It is degradable and can be gradually degraded in the body and metabolized by the organism without causing adverse effects on tissues and organs, meeting the requirements of biomedical materials. The biodegradable piezoelectric material is combined with ultrasonic technology. When the piezoelectric hydrogel is used as a wound dressing and attached to an epidermal wound, a large amount of active oxygen is generated by the piezoelectric material through ultrasound induction. The active oxygen can quickly kill bacteria from the wound, thereby achieving epidermal wound repair.

[0014] In a feasible implementation, the mass ratio of the potassium sodium niobate powder to the polydopamine powder is (0.5-2):(0.1-0.5);

[0015] The mass ratio of the potassium sodium niobate modified with polydopamine on the surface to the polylactic acid powder is (0.5-2):(0.5~2);

[0016] The mass ratio of the mixture of potassium sodium niobate and polylactic acid modified with polydopamine on the surface, the methacryloyl gelatin, the carboxymethyl chitosan, the epidermal growth factor and the glycerol is (1-5):(80-160):(0.1-0.5):(0.1-0.5):(40-80);

[0017] The first organic solvent is selected from at least one of isopropanol, butanediol and ethanol.

[0018] In a feasible implementation, the potassium sodium niobate is prepared by a method comprising the following steps:

[0019] The potassium chloride, potassium carbonate and niobium pentoxide are uniformly mixed and calcined at 800°C to 1200°C for 3h to 6h to obtain a potassium sodium niobate precursor;

[0020] The potassium sodium niobate precursor is immersed in a nitric acid solution for 6 hours to 8 hours to obtain a potassium sodium niobate precursor after impurities are removed; and the potassium sodium niobate precursor after impurities are removed, sodium carbonate, sodium chloride, potassium chloride and potassium carbonate are calcined at 800° C. to 900° C. for 1 hour to 3 hours to obtain potassium sodium niobate.

[0021] In a feasible implementation, the polydopamine powder is prepared by a method comprising the following steps: dissolving dopamine in a buffer solution, then adding ethanol and mixing evenly, then performing solid-liquid separation and retaining the solid to obtain the polydopamine powder.

[0022] In a feasible implementation, the carboxymethyl chitosan is prepared by a method comprising the following steps:

[0023] Mixing chitosan and a second organic solvent uniformly, then adding an alkaline solution, and reacting sufficiently to obtain an alkalized carboxymethyl chitosan solution; and mixing the alkalized carboxymethyl chitosan solution and chloroacetic acid uniformly, and reacting sufficiently to obtain carboxymethyl chitosan;

[0024] Wherein, the second organic solvent is selected from at least one of isopropanol, dimethyl sulfoxide and acetone;

[0025] Wherein, the alkaline solution is sodium hydroxide solution.

[0026] In a feasible implementation, the methacryloyl gelatin is prepared by a method comprising the following steps:

[0027] Dissolving gelatin in water, fully swelling at room temperature and then dissolving at 50°C to 60°C, then dropping methacrylic anhydride and fully reacting at 50°C to 60°C, then adding 30°C to 40°C water to dilute and terminate the reaction, to obtain a methacrylated gelatin solution; and

[0028] The methacrylylated gelatin solution is dialyzed at 30° C. to 50° C. to remove unreacted monomers. After the dialysis is completed, the methacrylylated gelatin is obtained by vacuum freeze drying.

[0029] In a feasible implementation, the mixture of potassium sodium niobate and polylactic acid modified with polydopamine on the surface, methacrylated gelatin, carboxymethyl chitosan, epidermal growth factor and glycerol are dissolved in water, mixed evenly, and then a photocuring agent is added, mixed evenly, and then cross-linked. After sufficient reaction, the piezoelectric hydrogel is obtained by the following operation:

[0030] dissolving methacryloyl gelatin in water to obtain a methacryloyl gelatin solution;

[0031] Adding the mixture of sodium potassium niobate and polylactic acid modified with polydopamine on the surface, carboxymethyl chitosan and epidermal growth factor into the methacrylylated gelatin solution, and mixing them evenly to obtain a first mixed solution;

[0032] Adding glycerol to the first mixed solution, mixing evenly, adding a light curing agent, heating to 35° C. to 40° C. in a light-proof condition and mixing evenly to obtain a second mixed solution; and

[0033] The second mixed solution is subjected to a photo-crosslinking reaction under light-proof conditions, and a piezoelectric hydrogel is obtained after sufficient reaction.

[0034] An ultrasonic therapeutic device comprises the above-mentioned piezoelectric hydrogel and an ultrasonic transducer, wherein the ultrasonic transducer is located on the surface of the piezoelectric hydrogel.

[0035] The ultrasonic treatment device of the technical solution of the present invention combines piezoelectric hydrogel and ultrasonic waves. The ultrasonic transducer is used to provide ultrasonic waves. The piezoelectric material in the piezoelectric hydrogel is induced by ultrasound to generate a large amount of active oxygen. The active oxygen can quickly kill bacteria from the wound, thereby achieving epidermal wound repair. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Flow chart of a method for preparing a piezoelectric hydrogel according to one embodiment of the present invention;

[0037] Figure 2 The X-ray diffraction pattern of PLA / KNN-PDA prepared in Example 1 of the present invention;

[0038] Figure 3 This is an infrared spectrum of the piezoelectric hydrogel prepared in Example 1 of the present invention;

[0039] Figure 4 This is a scanning electron microscope (SEM) image of the piezoelectric hydrogel prepared in Example 1 of the present invention;

[0040] FIG5(a) and FIG5(b) are phase change diagrams of the piezoelectric hydrogel prepared in Example 1 of the present invention;

[0041] Figure 6 Comparison of the swelling rates of the piezoelectric hydrogel prepared in Example 1 of the present invention and the GelMa hydrogel prepared in Comparative Example 1;

[0042] Figure 7 The porosity comparison of the piezoelectric hydrogel prepared in Example 1 of the present invention and the GelMa hydrogel prepared in Comparative Example 1;

[0043] Figure 8 The biocompatibility of the piezoelectric hydrogel prepared in Example 1 of the present invention and the GelMa hydrogel prepared in Comparative Example 1 is compared. DETAILED DESCRIPTION

[0044] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0046] The present invention designs a piezoelectric hydrogel that can respond to ultrasound. Ultrasound is a high-frequency mechanical wave that has low energy attenuation and deep penetration distance when transmitting energy to subcutaneous tissue, and can directly act on subcutaneous tissue. The present invention combines biodegradable piezoelectric materials with ultrasonic technology, which can effectively regulate the time and intensity of electrical stimulation in the body, and can effectively promote the rapid healing and repair and regeneration of epidermal wounds. In addition, the piezoelectric hydrogel of the present invention can use the multi-network structure of the hydrogel to achieve drug loading, as a multifunctional hydrogel drug loading system.

[0047] The piezoelectric hydrogel of one embodiment includes methacrylated gelatin, sodium potassium niobate, polydopamine, polylactic acid, carboxymethyl chitosan, epidermal growth factor and glycerol, wherein polydopamine is modified on the surface of sodium potassium niobate, and sodium potassium niobate, polydopamine, polylactic acid, carboxymethyl chitosan, epidermal growth factor and glycerol are dispersed in the methacrylated gelatin.

[0048] In the piezoelectric hydrogel of this embodiment, methacrylated gelatin serves as a hydrogel matrix with a multi-network structure for carrying other functional substances; polylactic acid is a biodegradable piezoelectric polymer; potassium sodium niobate is a soluble piezoelectric material with excellent piezoelectric properties; the introduction of polydopamine for surface coating modification of potassium sodium niobate is beneficial to improving biocompatibility; carboxymethyl chitosan can help epidermal wounds to quickly stop bleeding and kill bacteria, and when the microenvironment of the epidermal wound reaches stability, with the continuous release of epidermal growth factor, it promotes the rapid proliferation and differentiation of epidermal cells, thereby achieving rapid healing and repair of the epidermal wound; epidermal growth factor can promote the rapid proliferation and differentiation of cells in the epidermal wound and accelerate the healing of the epidermal wound; glycerol is beneficial to improving the adhesion and moisturizing properties of the piezoelectric hydrogel.

[0049] The piezoelectric hydrogel of this embodiment presents a honeycomb porous structure with a pore size of about 100 microns to 200 microns. The honeycomb porous structure helps to improve the mechanical strength of the hydrogel and also provides a larger specific surface area, which is of great significance for the loading and release of nanomedicines. In addition, this pore size distribution is conducive to cell adhesion and proliferation, making piezoelectric hydrogels have broad application prospects in the fields of tissue engineering and regenerative medicine.

[0050] Based on the above-mentioned implementation mode, the mass ratio of methacryloyl gelatin, potassium sodium niobate, polydopamine, polylactic acid, carboxymethyl chitosan, epidermal growth factor and glycerol is (80-160):(0.5-2):(0.1-0.5):(0.5-1):(0.1-0.5):(0.1-0.5):(40-80).

[0051] The present invention combines biodegradable piezoelectric materials with ultrasonic technology. When the piezoelectric hydrogel is used as a wound dressing and attached to an epidermal wound, the piezoelectric material is induced by ultrasound to generate a large amount of active oxygen, which can quickly kill bacteria from the wound, thereby achieving epidermal wound repair.

[0052] In addition, the piezoelectric hydrogel of the present invention can also be used as a drug delivery carrier, cell growth scaffold, etc. By controlling the preparation conditions and adding different functional components, the piezoelectric hydrogel of the present invention can be endowed with multiple functions such as antibacterial, growth-promoting, and repair-promoting, thereby meeting various application requirements.

[0053] See also Figure 1 A method for preparing a piezoelectric hydrogel according to an embodiment of the present invention comprises the following steps:

[0054] S10, dissolving potassium sodium niobate powder and polydopamine powder in a buffer solution, performing solid-liquid separation after sufficient reaction and retaining the solid to obtain potassium sodium niobate with polydopamine modified on the surface.

[0055] In a feasible implementation, the mass ratio of potassium sodium niobate powder to polydopamine powder is (0.5-2):(0.1-0.5). Furthermore, the buffer solution may be a hydrochloric acid buffer solution.

[0056] In a feasible implementation, potassium sodium niobate is prepared by a method comprising the following steps:

[0057] The potassium chloride, potassium carbonate and niobium pentoxide are uniformly mixed and calcined at 800°C to 1200°C for 3h to 6h to obtain a potassium sodium niobate precursor;

[0058] Soaking the potassium sodium niobate precursor in a nitric acid solution for 6 hours to 8 hours to obtain a potassium sodium niobate precursor after impurities are removed; and

[0059] The impurity-removed potassium sodium niobate precursor, sodium carbonate, sodium chloride, potassium chloride and potassium carbonate are calcined at 800° C. to 900° C. for 1 h to 3 h to obtain potassium sodium niobate.

[0060] The concentration of the nitric acid solution is 2 mol / L to 6 mol / L. After the potassium sodium niobate precursor is soaked in the nitric acid solution for 6 to 8 hours, the soaked product can be repeatedly washed with deionized water and then transferred to a constant temperature oven for drying. The drying temperature and time in the constant temperature oven are not limited, for example, the temperature can be 60°C and the drying time can be 12 hours.

[0061] In a feasible implementation, polydopamine powder is prepared by a method comprising the following steps: dissolving dopamine in a buffer solution, then adding ethanol to mix evenly, then performing solid-liquid separation and retaining the solid to obtain polydopamine powder. Among them, ethanol can control the degree of polymerization and molecular weight distribution of dopamine and accelerate the reaction rate. Among them, the buffer solution can be a Tirs buffer system, a copper sulfate / hydrogen peroxide buffer system, etc.

[0062] S20, dissolving the potassium sodium niobate surface modified with polydopamine and polylactic acid powder obtained in step S10 in a first organic solvent, mixing them evenly, performing solid-liquid separation and retaining the solid to obtain a mixture of potassium sodium niobate surface modified with polydopamine and polylactic acid.

[0063] In a feasible implementation, the mass ratio of potassium sodium niobate surface-modified with polydopamine and polylactic acid powder is (1-4):(0.2-1).

[0064] In a feasible implementation, the first organic solvent is selected from at least one of isopropanol, butanediol and methanol.

[0065] S30, dissolving the mixture of sodium potassium niobate and polylactic acid with surface modification of polydopamine obtained in step S20, methacrylated gelatin, carboxymethyl chitosan, epidermal growth factor and glycerol in water, adding a photocuring agent after mixing evenly, performing a cross-linking reaction after mixing evenly, and obtaining a piezoelectric hydrogel after sufficient reaction.

[0066] In a feasible implementation, the mass ratio of a mixture of potassium sodium niobate surface modified with polydopamine and polylactic acid, methacrylated gelatin, carboxymethyl chitosan, epidermal growth factor and glycerol is (1-5):(80-160):(0.1-0.5):(0.1-0.5):(40-80).

[0067] In a feasible implementation, carboxymethyl chitosan is prepared by a method comprising the following steps:

[0068] Mixing chitosan and a second organic solvent uniformly, then adding an alkaline solution, and reacting sufficiently to obtain an alkalized carboxymethyl chitosan solution; and

[0069] The alkalized carboxymethyl chitosan solution is mixed evenly with chloroacetic acid, and the carboxymethyl chitosan is obtained after sufficient reaction.

[0070] In this embodiment, the alkalized carboxymethyl chitosan and chloroacetic acid undergo a carboxymethylation reaction to generate carboxymethyl chitosan. The second organic solvent is selected from at least one of isopropanol, dimethyl sulfoxide and acetone. The alkaline solution is a sodium hydroxide solution.

[0071] In a feasible implementation, the methacryloyl gelatin is prepared by a method comprising the following steps:

[0072] Dissolving gelatin in water, fully swelling at room temperature and then dissolving at 50°C to 60°C, then dropping methacrylic anhydride and fully reacting at 50°C to 60°C, then adding 30°C to 40°C water to dilute and terminate the reaction, to obtain a methacrylated gelatin solution; and

[0073] The methacrylylated gelatin solution is dialyzed at 30° C. to 50° C. to remove unreacted monomers. After the dialysis is completed, the methacrylylated gelatin is obtained by vacuum freeze drying.

[0074] In a feasible implementation, a mixture of sodium potassium niobate and polylactic acid modified with polydopamine on the surface, methacrylated gelatin, carboxymethyl chitosan, epidermal growth factor and glycerol are dissolved in water, mixed evenly, and then a photocuring agent is added. The operation of obtaining a piezoelectric hydrogel after cross-linking is as follows:

[0075] dissolving methacryloyl gelatin in water to obtain a methacryloyl gelatin solution;

[0076] Adding a mixture of sodium potassium niobate and polylactic acid modified with polydopamine on the surface, carboxymethyl chitosan and epidermal growth factor into the methacrylylated gelatin solution, and mixing them evenly to obtain a first mixed solution;

[0077] Adding glycerol to the first mixed solution, mixing evenly, adding a light curing agent, heating to 35° C. to 40° C. in a light-proof condition and mixing evenly to obtain a second mixed solution; and

[0078] The second mixed solution is subjected to a photo-crosslinking reaction under light-proof conditions to obtain a piezoelectric hydrogel.

[0079] The photocuring agent may be LAP or 2959. The photocrosslinking reaction of the second mixed solution under light-proof conditions refers to the photocrosslinking reaction performed by irradiating with ultraviolet light under the condition of avoiding other light except the light required for the photocrosslinking.

[0080] The preparation method of the piezoelectric hydrogel of the technical solution of the present invention is simple in process. The prepared piezoelectric hydrogel has good biocompatibility, is compatible with biological tissues, and supports cell adhesion, proliferation and differentiation, and is suitable for biomedical applications. It is degradable and can be gradually degraded in the body and metabolized by the organism without causing adverse effects on tissues and organs, meeting the requirements of biomedical materials. The biodegradable piezoelectric material is combined with ultrasonic technology. When the piezoelectric hydrogel is used as a wound dressing and attached to an epidermal wound, a large amount of active oxygen is generated by the piezoelectric material through ultrasound induction. The active oxygen can quickly kill bacteria from the wound, thereby achieving epidermal wound repair.

[0081] An ultrasonic therapeutic device in one embodiment includes a piezoelectric hydrogel and an ultrasonic transducer, wherein the ultrasonic transducer is located on the surface of the piezoelectric hydrogel. Specifically, the ultrasonic transducer and the piezoelectric hydrogel are adhered together by a backing tape, and an isolation layer is provided on the side of the piezoelectric hydrogel away from the ultrasonic transducer for protection. When it is needed, the isolation layer is removed, and the piezoelectric hydrogel side of the ultrasonic therapeutic device is attached to the desired treatment part of the body, such as the location of an epidermal wound.

[0082] The ultrasonic treatment device of the technical solution of the present invention combines piezoelectric hydrogel and ultrasonic waves. The ultrasonic transducer is used to provide ultrasonic waves. The piezoelectric material in the piezoelectric hydrogel is induced by ultrasound to generate a large amount of active oxygen. The active oxygen can quickly kill bacteria from the wound, thereby achieving epidermal wound repair.

[0083] With reference to the above implementation contents, in order to make the technical solution of the present invention more specific, clear and easy to understand, the technical solution of the present invention is now exemplified. However, it should be noted that the contents to be protected by the present invention are not limited to the following embodiments.

[0084] Example 1

[0085] Embodiment 1 provides a piezoelectric hydrogel and a preparation method thereof, comprising the following steps:

[0086] 1. Synthesis of potassium sodium niobate (KNN for short)

[0087] Step 1.1: 29.84 g of KCl, 2.764 g of potassium carbonate, and 10.63 g of niobium pentoxide were weighed using an analytical balance, the three powders were ground and mixed using a high-energy ball mill, and calcined in a crucible at 1000° C. for 3 h to obtain a potassium sodium niobate precursor;

[0088] Step 1.2: Pour the potassium sodium niobate precursor into a 4 mol / L nitric acid solution and soak for 6 hours, wash the product three times with deionized water, and transfer it to an oven at a constant temperature of 60°C and dry it for 12 hours;

[0089] Step 1.3: Weigh 1 g of the above product, sodium carbonate (3 g), sodium chloride (0.3 g), potassium chloride (3 g) and potassium carbonate (0.3 g) and calcine them in a crucible at 800° C. for 60 minutes;

[0090] Step 1.4: After repeated washing and multiple centrifugation, the final product is transferred into a constant temperature oven and dried at 60° C. for 12 h to obtain potassium sodium niobate.

[0091] 2. Synthesis of potassium sodium niobate modified with polydopamine (KNN-PDA)

[0092] Step 2.1: Weigh 0.05 g of DA, dissolve it in 100 mL of Tirs buffer (10 mM, pH 8.5), then add 20 mL of ethanol and stir evenly; continue stirring and reacting for 6 h at room temperature, wash it with water three times by centrifugation (10000 rpm, 10 min), and dry it in an oven at 60 ° C for 12 h to obtain PDA powder;

[0093] Step 2.2: Weigh 1 g of KNN powder material, dissolve it in a hydrochloric acid buffer solution (200 mL, 1 mM, pH 8.6), and stir to react for 1 h;

[0094] Step 2.3: Weigh 0.1 g of PDA powder, add it to the above mixture solution and continue stirring for 4 hours;

[0095] Step 2.4: The mixed solution was repeatedly washed and centrifuged for multiple times, and the final product was transferred to a vacuum oven and dried for 12 h to obtain KNN@PDA.

[0096] 3. Synthesis of a mixture of potassium sodium niobate and polylactic acid modified with polydopamine (referred to as PLA / KNN-PDA)

[0097] Step 3.1: Weigh 1 g of KNN-PDA and add it to hexafluoroisopropanol (10 mL), and stir until uniform;

[0098] Step 3.2: Weigh 1 g of polylactic acid powder and add it to the above solution. Stir and react for 1 hour. Wash the mixed solution repeatedly and centrifuge it several times. Transfer the final product to a vacuum oven and dry it for 12 hours to obtain PLA / KNN-PDA.

[0099] 4. Synthesis of carboxymethyl chitosan (CMCS)

[0100] Step 4.1: Weigh 1 g of chitosan, add it to 10 ml of isopropanol, stir evenly, and soak for several hours; add the above solution to 20 ml of sodium hydroxide solution, and react for 1 hour to obtain an alkaline carboxymethyl chitosan solution;

[0101] Step 4.2: 5 mL of chloroacetic acid is added to the alkalized carboxymethyl chitosan solution to carry out carboxymethylation reaction, the reaction temperature is controlled between 60°C and 70°C, and the reaction is terminated after 1 hour;

[0102] Step 4.3: The reaction product is repeatedly washed three times with ethanol, then placed in a vacuum drying oven for drying, and finally ground with a mortar to produce carboxymethyl chitosan.

[0103] 5. Synthesis of methacryloyl gelatin (GelMA)

[0104] Step 5.1: Weigh 5 g of gelatin (manufacturer: Merck Sigma) and dissolve it in 200 mL of 40°C deionized water and swell it at room temperature for 1 hour;

[0105] Step 5.2: Stir and dissolve at 50°C for 1 hour, then slowly drop 8 mL of methacrylic anhydride, react at 50°C for 4 hours with continuous stirring;

[0106] Step 5.3: Add 200 mL of 40° C. deionized water to dilute and terminate the reaction to obtain a methacrylated gelatin solution;

[0107] Step 5.4: The methacrylated gelatin solution is then placed into a dialysis bag (molecular weight of 8000-14000), and the dialysis bag is placed in deionized water at 50° C. for 7 days to remove unreacted monomers, and the water is changed every 4 hours or so;

[0108] Step 5.5: The dialyzed solution was transferred to a petri dish for cooling, and the methacryloyl gelatin was collected by vacuum freeze drying.

[0109] 6. Preparation of piezoelectric hydrogel (abbreviated as PLA / KNN-PDA / CMCS / EGF / Gl / GelMA)

[0110] Step 6.1: Weigh 0.1 g of GelMA and dissolve it in 2 mL of deionized water to prepare a GelMA solution;

[0111] Step 6.2: Weigh 0.1 g of PLA / KNN-PDA, 0.05 g of CMCS, and 0.01 g of EGF, add them to the GelMA solution in batches and stir slowly for 3 hours;

[0112] Step 6.3: Pipette 200 μL of glycerol into the mixture and quickly stir the mixture evenly;

[0113] Step 6.4: Add 0.2 g of light curing agent (LAP), heat to 35°C and stir for 5 minutes in a completely dark environment;

[0114] Step 6.5: Use a disposable sterile medical needle to draw up the mixed solution and add it into a plastic mold with a diameter of 15 mm;

[0115] Step 6.6: Under the condition of complete light avoidance, irradiate with ultraviolet light to carry out photo-crosslinking reaction, so as to obtain the piezoelectric hydrogel of Example 1.

[0116] Example 2

[0117] 1. Synthesis of potassium sodium niobate (KNN for short)

[0118] Step 1.1: 29.84 g of KCl, 1.38 g of potassium carbonate, and 5.32 g of niobium pentoxide were weighed using an analytical balance, the three powders were ground and mixed using a high-energy ball mill, and calcined in a crucible at 1000° C. for 3 h to obtain a potassium sodium niobate precursor;

[0119] Step 1.2: Pour the potassium sodium niobate precursor into a 2 mol / L nitric acid solution and soak for 6 hours, wash the product three times with deionized water, and transfer it to an oven at a constant temperature of 60°C and dry it for 12 hours;

[0120] Step 1.3: Weigh 0.5 g of the above product, sodium carbonate (3 g), sodium chloride (0.3 g), potassium chloride (3 g) and potassium carbonate (0.3 g) and calcine in a crucible at 800° C. for 60 minutes;

[0121] Step 1.4: After repeated washing and multiple centrifugation, the final product is transferred into a constant temperature oven and dried at 60° C. for 12 h to obtain potassium sodium niobate.

[0122] 2. Synthesis of potassium sodium niobate modified with polydopamine (KNN-PDA)

[0123] Step 2.1: Weigh 0.05 g of DA, dissolve it in 100 mL of Tirs buffer (10 mM, pH 8.5), then add 20 mL of ethanol and stir evenly; continue stirring and reacting for 6 h at room temperature, wash it with water three times by centrifugation (10000 rpm, 10 min), and dry it in an oven at 60 ° C for 12 h to obtain PDA powder;

[0124] Step 2.2: Weigh 1 g of KNN powder material, dissolve it in a hydrochloric acid buffer solution (200 mL, 1 mM, pH 8.6), and stir to react for 1 h;

[0125] Step 2.3: Weigh 0.1 g of PDA powder, add it to the above mixture solution and continue stirring for 4 hours;

[0126] Step 2.4: The mixed solution was repeatedly washed and centrifuged for multiple times, and the final product was transferred to a vacuum oven and dried for 12 h to obtain KNN@PDA.

[0127] 3. Synthesis of a mixture of potassium sodium niobate and polylactic acid modified with polydopamine (referred to as PLA / KNN-PDA)

[0128] Step 3.1: Weigh 1 g of KNN-PDA and add it to hexafluoroisopropanol (10 mL), and stir until uniform;

[0129] Step 3.2: Weigh 1 g of polylactic acid powder and add it to the above solution. Stir and react for 1 hour. Wash the mixed solution repeatedly and centrifuge it several times. Transfer the final product to a vacuum oven and dry it for 12 hours to obtain PLA / KNN-PDA.

[0130] 4. Synthesis of carboxymethyl chitosan (CMCS)

[0131] Step 4.1: Weigh 1 g of chitosan, add it to 10 ml of isopropanol, stir evenly, and soak for several hours; add the above solution to 20 ml of sodium hydroxide solution, and react for 1 hour to obtain an alkaline carboxymethyl chitosan solution;

[0132] Step 4.2: 5 mL of chloroacetic acid is added to the alkalized carboxymethyl chitosan solution to carry out carboxymethylation reaction, the reaction temperature is controlled between 60°C and 70°C, and the reaction is terminated after 1 hour;

[0133] Step 4.3: The reaction product is repeatedly washed three times with ethanol, then placed in a vacuum drying oven for drying, and finally ground with a mortar to produce carboxymethyl chitosan.

[0134] 5. Synthesis of methacryloyl gelatin (GelMA)

[0135] Step 5.1: Weigh 5 g of gelatin (manufacturer: Merck Sigma) and dissolve it in 200 mL of 40°C deionized water and swell it at room temperature for 1 hour;

[0136] Step 5.2: Stir and dissolve at 50°C for 1 hour, then slowly drop 8 mL of methacrylic anhydride, react at 50°C for 4 hours with continuous stirring;

[0137] Step 5.3: Add 200 mL of 40° C. deionized water to dilute and terminate the reaction to obtain a methacrylated gelatin solution;

[0138] Step 5.4: The methacrylated gelatin solution is then placed in a dialysis bag, and the dialysis bag is placed in deionized water at 50° C. for 7 days to remove unreacted monomers, and the water is changed every 4 hours or so;

[0139] Step 5.5: The dialyzed solution was transferred to a petri dish for cooling, and the methacryloyl gelatin was collected by vacuum freeze drying.

[0140] 6. Preparation of piezoelectric hydrogel (abbreviated as PLA / KNN-PDA / CMCS / EGF / Gl / GelMA)

[0141] Step 6.1: Weigh 0.1 g of GelMA and dissolve it in 2 mL of deionized water to prepare a GelMA solution;

[0142] Step 6.2: Weigh 0.05 g of PLA / KNN-PDA, 0.025 g of CMCS, and 0.005 g of EGF, add them to the GelMA solution in batches and stir slowly for 3 hours;

[0143] Step 6.3: Pipette 100 μL of glycerol into the mixture and quickly stir the mixture evenly;

[0144] Step 6.4: Add 0.2 g of light curing agent (LAP), heat to 35°C and stir for 5 minutes in a completely dark environment;

[0145] Step 6.5: Use a disposable sterile medical needle to draw up the mixed solution and add it into a plastic mold with a diameter of 15 mm;

[0146] Step 6.6: Under the condition of complete light avoidance, irradiate with ultraviolet light to carry out photo-crosslinking reaction, so as to obtain the piezoelectric hydrogel of Example 2.

[0147] Example 3

[0148] 1. Synthesis of potassium sodium niobate (KNN for short)

[0149] Step 1.1: 29.84 g of KCl, 5.53 g of potassium carbonate, and 21.2 g of niobium pentoxide were weighed using an analytical balance, the three powders were ground and mixed using a high-energy ball mill, and calcined in a crucible at 1000° C. for 3 h to obtain a potassium sodium niobate precursor;

[0150] Step 1.2: Pour the potassium sodium niobate precursor into a nitric acid solution with a concentration of 6 mol / L and soak for 6 hours, wash the product three times with deionized water, and transfer it to an oven at a constant temperature of 60°C and dry it for 12 hours;

[0151] Step 1.3: Weigh 1.5 g of the above product, sodium carbonate (3 g), sodium chloride (0.3 g), potassium chloride (3 g) and potassium carbonate (0.3 g) and calcine them in a crucible at 800° C. for 60 minutes;

[0152] Step 1.4: After repeated washing and multiple centrifugation, the final product is transferred into a constant temperature oven and dried at 60° C. for 12 h to obtain potassium sodium niobate.

[0153] 2. Synthesis of potassium sodium niobate modified with polydopamine (KNN-PDA)

[0154] Step 2.1: Weigh 0.05 g of DA, dissolve it in 100 mL of Tirs buffer (10 mM, pH 8.5), then add 20 mL of ethanol and stir evenly; continue stirring and reacting for 6 h at room temperature, wash it with water three times by centrifugation (10000 rpm, 10 min), and dry it in an oven at 60 ° C for 12 h to obtain PDA powder;

[0155] Step 2.2: Weigh 1 g of KNN powder material, dissolve it in a hydrochloric acid buffer solution (200 mL, 1 mM, pH 8.6), and stir to react for 1 h;

[0156] Step 2.3: Weigh 0.1 g of PDA powder, add it to the above mixture solution and continue stirring for 4 hours;

[0157] Step 2.4: The mixed solution was repeatedly washed and centrifuged for multiple times, and the final product was transferred to a vacuum oven and dried for 12 h to obtain KNN@PDA.

[0158] 3. Synthesis of a mixture of potassium sodium niobate and polylactic acid modified with polydopamine (referred to as PLA / KNN-PDA)

[0159] Step 3.1: Weigh 1 g of KNN-PDA and add it to hexafluoroisopropanol (10 mL), and stir until uniform;

[0160] Step 3.2: Weigh 1 g of polylactic acid powder and add it to the above solution. Stir and react for 1 hour. Wash the mixed solution repeatedly and centrifuge it several times. Transfer the final product to a vacuum oven and dry it for 12 hours to obtain PLA / KNN-PDA.

[0161] 4. Synthesis of carboxymethyl chitosan (CMCS)

[0162] Step 4.1: Weigh 1 g of chitosan, add it to 10 ml of isopropanol, stir evenly, and soak for several hours; add the above solution to 20 ml of sodium hydroxide solution, and react for 1 hour to obtain an alkaline carboxymethyl chitosan solution;

[0163] Step 4.2: 5 mL of chloroacetic acid is added to the alkalized carboxymethyl chitosan solution to perform carboxymethylation reaction, the reaction temperature is controlled between 60-70°C, and the reaction is terminated after 1 hour;

[0164] Step 4.3: The reaction product is repeatedly washed three times with ethanol, then placed in a vacuum drying oven for drying, and finally ground with a mortar to produce carboxymethyl chitosan.

[0165] 5. Synthesis of methacryloyl gelatin (GelMA)

[0166] Step 5.1: Weigh 5 g of gelatin (manufacturer: Merck Sigma) and dissolve it in 200 mL of 40°C deionized water and swell it at room temperature for 1 hour;

[0167] Step 5.2: Stir and dissolve at 50°C for 1 hour, then slowly drop 8 mL of methacrylic anhydride, react at 50°C for 4 hours with continuous stirring;

[0168] Step 5.3: Add 200 mL of 40° C. deionized water to dilute and terminate the reaction to obtain a methacrylated gelatin solution;

[0169] Step 5.4: The methacrylated gelatin solution is then placed in a dialysis bag, and the dialysis bag is placed in deionized water at 50° C. for 7 days to remove unreacted monomers, and the water is changed every 4 hours or so;

[0170] Step 5.5: The dialyzed solution was transferred to a petri dish for cooling, and the methacryloyl gelatin was collected by vacuum freeze drying.

[0171] 6. Preparation of piezoelectric hydrogel (abbreviated as PLA / KNN-PDA / CMCS / EGF / Gl / GelMA)

[0172] Step 6.1: Weigh 0.1 g of GelMA and dissolve it in 2 mL of deionized water to prepare a GelMA solution;

[0173] Step 6.2: Weigh 0.2 g of PLA / KNN-PDA, 0.1 g of CMCS, and 0.02 g of EGF, add them to the GelMA solution in batches and stir slowly for 3 hours;

[0174] Step 6.3: Pipette 300 μL of glycerol into the mixture and quickly stir the mixture evenly;

[0175] Step 6.4: Add 0.2 g of light curing agent (LAP), heat to 35°C and stir for 5 minutes in a completely dark environment;

[0176] Step 6.5: Use a disposable sterile medical needle to draw up the mixed solution and add it into a plastic mold with a diameter of 15 mm;

[0177] Step 6.6: Under the condition of complete light avoidance, irradiate with ultraviolet light to carry out photo-crosslinking reaction, so as to obtain the piezoelectric hydrogel of Example 3.

[0178] Comparative Example 1

[0179] This comparative example is a comparative example of Example 1, and provides a methacryloyl gelatin (GelMA for short) and a preparation method thereof, which is exactly the same as the preparation method of GelMA in Example 1.

[0180] Performance Testing:

[0181] (1) X-ray diffraction (XRD) test was performed on the PLA / KNN-PDA of Example 1, and the Figure 2 .from Figure 2 It can be seen that the corresponding diffraction peaks in the figure are (110), (111), (220), (221) and (003), respectively, indicating that KNN has a cubic phase structure.

[0182] (2) The components of the piezoelectric hydrogel prepared in Example 1 were characterized by Fourier transform infrared spectroscopy (FTIR), and the Figure 3 .from Figure 3 It can be seen that the amide A band peak is at 3280 cm and the amide B band peak is at 3072 cm, which are mainly related to NH stretching vibration; -1 The amide I band is at 1541 cm-1, which is caused by the stretching vibration of C=O. -1 The amide II band peak is at 1235cm, which is the coupling of NH bending vibration and CN stretching vibration; -1 It is the amide III band peak, which is caused by the CN stretching vibration and NH bending vibration of the amide bond.

[0183] (3) The piezoelectric hydrogel prepared in Example 1 was characterized by scanning electron microscopy (SEM), and the Figure 4 .Depend on Figure 4 It can be seen that the piezoelectric hydrogel prepared in Example 1 is a honeycomb-shaped porous material with a pore size of about 100 microns to 200 microns.

[0184] (4) The piezoelectric hydrogel of Example 1 was photographed before and after ultraviolet light irradiation during the preparation process to obtain Figures 5(a) and 5(b), wherein Figure 5(a) is a photograph before ultraviolet light irradiation, and Figure 5(b) is a photograph after ultraviolet light irradiation. It can be seen from Figures 5(a) and 5(b) that after the cross-linking reaction after ultraviolet light irradiation, the sol in the mold is successfully transformed into a gel state. This phase change clearly shows the curing process of the hydrogel under the action of ultraviolet light. Ultraviolet light cross-linking allows the sol to be rapidly transformed into a gel with certain mechanical strength and elasticity, ensuring the shape and structural stability of the piezoelectric hydrogel. This property is crucial for the practical application of hydrogels as wound dressings.

[0185] (5) The piezoelectric hydrogel (PLA / KNN-PDA / CMCS / EGF / Gl / GelMA) prepared in Example 1 and the GelMA in Comparative Example 1 were freeze-dried, and about 100 mg of each sample (denoted as W1) was immersed in a beaker containing 100 mL of phosphate buffer solution at room temperature. The samples were taken out at a certain time interval, and the water on the surface of the hydrogel was absorbed by filter paper and then weighed. The weight was represented by W2, according to the formula: Calculate the swelling ratio and get Figure 6 .like Figure 6 As shown, the swelling rates of GelMA of Comparative Example 1 and the piezoelectric hydrogel of Example 1 are 492% and 536%, respectively. It can be found that the piezoelectric hydrogel of Example 1 has better swelling performance, because carboxymethyl chitosan and glycerol can reduce the pore size of the gel, increase the specific surface area of ​​the hydrogel, increase the water swelling behavior, reduce the flexibility, and thus increase the swelling rate.

[0186] (6) Weigh a certain volume of ethanol (referred to as V1), and then soak the GelMA prepared in Comparative Example 1 and the piezoelectric hydrogel (PLA / KNN-PDA / CMCS / EGF / Gl / GelMA) prepared in Example 1 in the ethanol. The total volume of the sample and ethanol is recorded as V2. After soaking for several hours, take out the sample and record the volume at this time (referred to as V3), and then calculate the porosity according to the following formula: get Figure 7 .like Figure 7 As shown, the porosity of the GelMA prepared in Comparative Example 1 and the piezoelectric hydrogel prepared in Example 1 are 72.6% and 61.4%, respectively. It can be seen that compared with the GelMA in Comparative Example 1, when the piezoelectric material and the high molecular polymer are added to the porous structure, the porosity will be reduced to a certain extent. The porosity before the piezoelectric material is installed is 72.6%, indicating that the porosity is large and the piezoelectric material can be installed; the porosity after the piezoelectric material is installed is 61.4%, indicating that the piezoelectric material has entered the porous structure.

[0187] (7) The piezoelectric hydrogel (PLA / KNN-PDA / CMCS / EGF / Gl / GelMA) prepared in Example 1 and the GelMA in Comparative Example 1 were subjected to a biocompatibility test. The piezoelectric hydrogel in Example 1 and the GelMA in Comparative Example 1 were directly contacted with L929 cells to determine the cytotoxicity of the nanocomposite hydrogel. Figure 8 .like Figure 8 As shown, both hydrogels have no cytotoxicity to L929 cells, and in the piezoelectric hydrogel of Example 1, the viability of L929 cells is increased due to the addition of multiple polymer components.

[0188] (8) The antibacterial activity of the piezoelectric hydrogel prepared in Example 1 against Staphylococcus aureus was detected by the inhibition zone method. The specific steps are as follows: 50 μL of Staphylococcus aureus (10 6 CFU / mL) were evenly dispersed on the agar plate, the piezoelectric hydrogel was placed in a mold for solidification to obtain a hydrogel material with a diameter of 15 mm, the material was clamped with tweezers and placed on a plate, and ultrasonicated for 10 min respectively. The culture medium was placed in a carbon dioxide incubator at 37.5°C, and the diameter of the inhibition zone was measured after 24 h. The antibacterial performance of the piezoelectric hydrogel was evaluated by comparing the diameters of the inhibition zones. The diameter of the inhibition zone was the average of 3 parallel experiments. The results are shown in Table 1.

[0189] Table 1

[0190] Group Inhibition zone diameter Experiment 1 26.82mm Experiment 2 27.17mm Experiment 3 27.49mm average value 27.16mm

[0191] As can be seen from Table 1, the piezoelectric hydrogel of Example 1 has significant antibacterial activity against Staphylococcus aureus, further indicating that it has the possibility of being applied to epidermal wound repair.

[0192] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0193] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A piezoelectric hydrogel, characterized in that: The piezoelectric hydrogel includes methacrylated gelatin, sodium potassium niobate, polydopamine, polylactic acid, carboxymethyl chitosan, epidermal growth factor and glycerol, wherein the polydopamine is modified on the surface of the sodium potassium niobate, and the sodium potassium niobate, the polydopamine, the polylactic acid, the carboxymethyl chitosan, the epidermal growth factor and the glycerol are dispersed in the methacrylated gelatin.

2. The piezoelectric hydrogel according to claim 1, characterized in that: The mass ratio of the methacryloylated gelatin, the potassium sodium niobate, the polydopamine, the polylactic acid, the carboxymethyl chitosan, the epidermal growth factor and the glycerol is (80-160):(0.5-2):(0.1-0.5):(0.5-1):(0.1-0.5):(0.1-0.5):(40-80).

3. A method for preparing a piezoelectric hydrogel, characterized in that: The steps include: The potassium sodium niobate powder and the polydopamine powder are dissolved in a buffer solution, and after sufficient reaction, solid-liquid separation is performed and the solid is retained to obtain potassium sodium niobate with the surface modified with polydopamine; Dissolving the potassium sodium niobate with polydopamine on the surface and polylactic acid powder in a first organic solvent, mixing them evenly, performing solid-liquid separation and retaining the solid to obtain a mixture of potassium sodium niobate with polydopamine on the surface and polylactic acid; and The mixture of sodium potassium niobate and polylactic acid modified with polydopamine on the surface, methacrylated gelatin, carboxymethyl chitosan, epidermal growth factor and glycerol are dissolved in water, mixed evenly, and then a photocuring agent is added, mixed evenly, and then a cross-linking reaction is carried out, and a piezoelectric hydrogel is obtained after sufficient reaction.

4. The method for preparing the piezoelectric hydrogel according to claim 3, characterized in that: The mass ratio of the potassium sodium niobate powder to the polydopamine powder is (0.5-2):(0.1-0.5); The mass ratio of the potassium sodium niobate modified with polydopamine on the surface to the polylactic acid powder is (0.5-2):(0.5~2); The mass ratio of the mixture of potassium sodium niobate and polylactic acid modified with polydopamine on the surface, the methacryloyl gelatin, the carboxymethyl chitosan, the epidermal growth factor and the glycerol is (1-5):(80-160):(0.1-0.5):(0.1-0.5):(40-80); The first organic solvent is selected from at least one of isopropanol, butanediol and ethanol.

5. The method for preparing the piezoelectric hydrogel according to claim 3, characterized in that: The potassium sodium niobate is prepared by a method comprising the following steps: The potassium chloride, potassium carbonate and niobium pentoxide are uniformly mixed and calcined at 800°C to 1200°C for 3h to 6h to obtain a potassium sodium niobate precursor; The potassium sodium niobate precursor is immersed in a nitric acid solution for 6 hours to 8 hours to obtain a potassium sodium niobate precursor after impurities are removed; and the potassium sodium niobate precursor after impurities are removed, sodium carbonate, sodium chloride, potassium chloride and potassium carbonate are calcined at 800° C. to 900° C. for 1 hour to 3 hours to obtain potassium sodium niobate.

6. The method for preparing the piezoelectric hydrogel according to claim 3, characterized in that: The polydopamine powder is prepared by a method comprising the following steps: dissolving dopamine in a buffer solution, then adding ethanol and mixing evenly, then performing solid-liquid separation and retaining the solid to obtain the polydopamine powder.

7. The method for preparing the piezoelectric hydrogel according to claim 3, characterized in that: The carboxymethyl chitosan is prepared by a method comprising the following steps: Mixing chitosan and a second organic solvent uniformly, then adding an alkaline solution, and reacting sufficiently to obtain an alkalized carboxymethyl chitosan solution; and mixing the alkalized carboxymethyl chitosan solution and chloroacetic acid uniformly, and reacting sufficiently to obtain carboxymethyl chitosan; Wherein, the second organic solvent is selected from at least one of isopropanol, dimethyl sulfoxide and acetone; Wherein, the alkaline solution is sodium hydroxide solution.

8. The method for preparing the piezoelectric hydrogel according to claim 3, characterized in that: The methacryloyl gelatin is prepared by a method comprising the following steps: Dissolving gelatin in water, fully swelling at room temperature and then dissolving at 50°C to 60°C, then dropping methacrylic anhydride and fully reacting at 50°C to 60°C, then adding 30°C to 40°C water to dilute and terminate the reaction, to obtain a methacrylated gelatin solution; and The methacrylylated gelatin solution is dialyzed at 30° C. to 50° C. to remove unreacted monomers. After the dialysis is completed, the methacrylylated gelatin is obtained by vacuum freeze drying.

9. The method for preparing the piezoelectric hydrogel according to claim 3, characterized in that: The mixture of sodium potassium niobate and polylactic acid modified with polydopamine on the surface, methacrylated gelatin, carboxymethyl chitosan, epidermal growth factor and glycerol are dissolved in water, mixed evenly, and then a photocuring agent is added, mixed evenly, and then cross-linked. After sufficient reaction, the piezoelectric hydrogel is obtained by the following operation: dissolving methacryloyl gelatin in water to obtain a methacryloyl gelatin solution; Adding the mixture of sodium potassium niobate and polylactic acid modified with polydopamine on the surface, carboxymethyl chitosan and epidermal growth factor into the methacrylylated gelatin solution, and mixing them evenly to obtain a first mixed solution; Adding glycerol to the first mixed solution, mixing evenly, adding a light curing agent, heating to 35° C. to 40° C. in a light-proof condition and mixing evenly to obtain a second mixed solution; and The second mixed solution is subjected to a photo-crosslinking reaction under light-proof conditions, and a piezoelectric hydrogel is obtained after sufficient reaction.

10. An ultrasonic therapeutic device, characterized in that: It comprises the piezoelectric hydrogel according to claim 1 or 2 and an ultrasonic transducer, wherein the ultrasonic transducer is located on the surface of the piezoelectric hydrogel.